Risk Factors of Infectious Complications after Flexible Uretero-renoscopy with Laser Lithotripsy - Senocak, Cagri; Ozcan, Cihat; Sahin, Tolga; Yilmaz, Gulden; Ozyuvali, Ekrem; Sarikaya, Selcuk; Resorlu, Berkan; Oguz, Ural; Bozkurt, Omer Faruk; Unsal, Ali; Adsan, Oztug (Urology Journal, 2018)
Purpose: To determine the perioperative risk factors for postoperative infections among patients undergoing flexible uretero-renoscopy with laser lithotripsy (FURSLL). In addition, the resistance patterns of pathogens isolated from positive preoperative urine cultures were investigated. Materials and Methods: We retrospectively reviewed data from 492 consecutive patients who had undergone FURSLL for stone disease in our department. Postoperative infection was defined as fever (? 38°C) with pyuria (? 10 white blood cells per high power field), or systemic inflammatory response syndrome, or sepsis. Pre-operative and intra-operative characteristics between patients with and without postoperative infectious complications were compared using univariate analyses. Significant variables on univariate analyses were included in a multivariate logistic regression analysis to evaluate risk factors associated with postoperative infection following FURSLL. Results: 42 (8.5%) of 492 patients had postoperative infectious complications after FURSLL. 59 (12%) of 492 patients had a positive preoperative urine culture. 19 (32.2% of 59) patients had multidrug resistance (MDR) isolates recovered from positive preoperative urine cultures. 75% (9/12 cultures) of the positive preoperative urine cultures of patients in whom a postoperative infectious complication developed consisted of gram-negative pathogens. On multivariate analysis positive preoperative MDR urine culture (OR:4.75;95%CI:1.55-14.56; P = .006) was found to be significant with the dependent variable as the postoperative infectious complications despite appropriate preoperative antibiotic therapy. Conclusion: We found that positive preoperative MDR urine culture is a significant risk factor for infectious complications after FURSLL. Our findings point to the need for further research on assessment of risk factors for MDR infections to reduce the rate of postoperative infectious complications.